Implementation of ICT-Based Problem-Based Learning Model to Improve Higher Order Thinking Skills in IPAS Learning in Madrasah Ibtidaiyah - Khairullina, Alifia; Prastowo, Andi (Departemen Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2024)
Transformation in the education system is needed to meet the needs of the 21st century, which emphasizes critical, creative, and collaborative thinking skills. This study aims to explore the implementation of the Problem-Based Learning (PBL) model based on Information and Communication Technology (ICT) in improving higher-order thinking Skills (HOTS) in learning Natural and Social Sciences (IPA) in West Lombok Madrasah Ibtidaiyah. This research used a descriptive qualitative method, with data collected through interviews, observations, documentation, and HOTS written tests. Data analysis used the theory of Miles and Huberman data reduction, condensation, data display and conclusion drawing. Students involved in this method are more motivated and active in learning, especially with ICT tools such as Quizizz and computer simulations that make it easier to understand learning concepts. The implementation of ICT-based PBL not only improves students' higher-order thinking skills but also makes learning more exciting and contextualized. Despite challenges such as limited technological infrastructure, this approach has significantly impacted learning in Madrasah Ibtidaiyah.